The Israeli war on Gaza (Research into geostrategic goals and dimensions) - Assistant Dr. Maitham Anidi Ali (Tikrit Journal For Political Science, 2024)
Operation (Al-Aqsa Flood) was launched on October 7, 2023, against the Zionist settlements in the occupied Palestinian territories, and sparked great controversy. The Palestinian attacks were preemptive, abortive, and revealed a Zionist project aimed at creating a canal called (Ben Gurion). Due to the difficult terrain and its high cost, the canal It will pass through Gaza, and this requires the liquidation of the opposing forces and the displacement of its population to ensure the security of the canal, which could change the global trade route by linking the Red Sea to the Mediterranean. This means that the (Israeli) war on Gaza carries within it geostrategic objectives at the geopolitical, geomilitary, and geographical policy levels. Geoeconomic, it will have geopolitical and demographic dimensions on the Arab region, navigation, and international trade. Therefore, the attacks of October 7 were abortive, and were in harmony with the reality of local challenges at the level of Zionist violations, at the Arab level and the reality of humiliating Arab normalization, and internationally, monopolizing the trinity of forces opposed to the current world order and American influence to gain material and moral support.